2014
DOI: 10.1177/0954008314555521
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behaviour and cure kinetic studies of a trifunctional phenylethynyl-terminated imide oligomer

Abstract: A phenylethynyl-terminated imide oligomer (PETI)was prepared from a triamine and 4-phenylethynylphthalic anhydride. The oligomer can be used to prepare high performance resin-based composite material via resin transfer moulding due to its low melt viscosity. The cured resin also exhibited excellent thermal stability with 5% weight loss at temperature above 531 C and higher glass transition temperature T g (410 C) than PETI series as a result of the introduction of star-branched units. The rheological propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…A similar temperature dependency was reported by Yang et al. 31 for a PETI oligomer with similarities to MHT-R but prepared from a triamine and 4-phenylethynylphthalic anhydride. MHT-R appears to exhibit slightly lower absolute viscosity numbers.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…A similar temperature dependency was reported by Yang et al. 31 for a PETI oligomer with similarities to MHT-R but prepared from a triamine and 4-phenylethynylphthalic anhydride. MHT-R appears to exhibit slightly lower absolute viscosity numbers.…”
Section: Resultssupporting
confidence: 83%
“…This is typical for thermally initiated phenylethynyl crosslinking and is similar to results obtained in previous studies on polymers with similar chemistries. 30,31 The total heat of reaction of MHT-R, ΔH is approximately 220 J/g, and hence lower than values for BMI (389 J/g) 32 and typical aeronautical grade amine cured epoxies (450 J/g). 33
Figure 1.Dynamic DSC-scans of MHT-R resin at a heating rate of 10℃/min.
…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…For these years, phenylethynyl‐terminated imides (PETIs) have been widely employed as matrices and adhesive for high temperature applications due to its unique thermal curing process to afford thermoset resin with outstanding mechanical strength and toughness . Therefore, PETIs oligomers have received sustained attention . In recent years, it was found that phenylethynyl‐endcapped oligomers with calculated molecular weights as low as 750 g mol −1 could be melted at 280 °C to give low viscous and stable molten fluid, showing good features for resin transfer molding (RTM) processing.…”
Section: Introductionmentioning
confidence: 99%
“…The heat flow of the sample as a function of temperature measured by differential scanning calorimetry (DSC) is extensively used as the raw data to study the cure kinetics. 5 9 The activation energy and kinetic parameters of curing process are all deduced from isothermal or nonisothermal DSC cures. 10,11 Isoconversion methods are the most commonly used and most reliable methods for obtaining activation energies of curing reactions.…”
Section: Introductionmentioning
confidence: 99%